Experimental and numerical investigation of stringer's 90° plies optimization of composite material stiffened panels. (June 2023) - Zhang, Xiulu; Miao, Huihui; Song, Wenjun; Li, Changyou; Lv, Guocheng; Fang, Caiwen
In this paper, the optimal design of I- and T-shaped stringer's 90° plies is investigated to improve the performance of composite stiffened panel's strength and curing deformation. A theoretical method is deduced to build the constitutive equations of curing and buckling, which indicates that the stringer's 90° plies play an important role in the curing deformation of the structure. The finite element method (FEM) is adopted to simulate the curing and instability path of the structure, and the simulation model's accuracy is verified by strain assurance criterion. In addition, the experimental analysis is performed by a series of I- and T-shaped specimens with different stringer's 90° plies. The good agreement between the results of theoretical method, FEM, and experiment confirms the reliability and feasibility of the analytical methods proposed in this paper. Furthermore, the optimal stringer's 90° plies ratio is explored. The curves fitted in this investigation reveal that in the stages of (I) and (II), the percentage of stringer's 90° plies θ has significant effect on curing deformation, while bearing capacity has little change. The reasonable range of θ is 5%∼20%, in which the bearing capacity and curing deformation reach the optimal solution. Therefore, the structures that are not sensitive to curing deformation are recommend to remove the stringer's 90° plies, which is benefit to reduce weight, optimize structural design and improve process quality. The results provide a reference to design I-, T-, L- and C- shaped composite panel.